2010
DOI: 10.1128/jcm.00921-10
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Bacillus cereus Group Strains To Cause Food Poisoning Varies According to Phylogenetic Affiliation (Groups I to VII) Rather than Species Affiliation

Abstract: Cytotoxic activity levels of culture filtrates and toxin distributions varied according to the phylogenetic group (I to VII) within the Bacillus cereus group, suggesting that these groups are of different clinical significance and are more suitable than species affiliations for determining food poisoning risk. A first-line, simple online tool (https://www.tools.symprevius.org/Bcereus/english.php) to assign strains to the different phylogenetic groups is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
206
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(223 citation statements)
references
References 24 publications
(21 reference statements)
14
206
0
3
Order By: Relevance
“…The pattern of toxin production for the strains isolated in the present case is presumably classical for strains implicated in emetic poisoning. Nevertheless, some emetic strains producing NHE were found to be very cytotoxic for Caco-2 cells, as previously reported (14). Furthermore, the simultaneous presence of the genetic determinants for cereulide and the genes encoding potential enterotoxins was recently demonstrated for a B. cereus strain (19,20), which appeared to be particularly virulent.…”
Section: Case Reportsupporting
confidence: 75%
“…The pattern of toxin production for the strains isolated in the present case is presumably classical for strains implicated in emetic poisoning. Nevertheless, some emetic strains producing NHE were found to be very cytotoxic for Caco-2 cells, as previously reported (14). Furthermore, the simultaneous presence of the genetic determinants for cereulide and the genes encoding potential enterotoxins was recently demonstrated for a B. cereus strain (19,20), which appeared to be particularly virulent.…”
Section: Case Reportsupporting
confidence: 75%
“…Amino acid sequence comparison and multiple-sequence alignment of CrdA, CrdB, and CrdC showed that these large proteins are made up of 35,19, and 16 copies of a 132-aa homologous domain, respectively (average sequence identity, 40 to 50% among the domains within and between proteins; Fig. 1; see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While their chromosomes are similar and syntenic, the different pathogenic properties and host specificities are often determined by plasmids (28,44,45). Altogether, the B. cereus group population has been well studied and can be divided into seven major phylogenetic clusters that correlate with ecological and toxicological properties and in which strains from the various "species" are intermixed (18,19,54).…”
mentioning
confidence: 99%
“…LM1212 proved to be closely related to Bt serovar konkukian strain 97-27 and to Bt serovar finitimus strain YBT-020. Both these strains cluster within the B. cereus group clade that contains B. anthracis, a clade variously described as 'group 1', 'group III', 'the anthrax clade' or the 'C clade' (Priest et al, 2004;Sorokin et al, 2006;Guinebretière et al, 2010;Raymond et al, 2010b). The PlcR-PapR and NprR-NprX systems (Perchat et al, 2011) of LM1212 were found identical to those of the anthrax-casing B. cereus G9241, although it contained no anthrax toxin genes and did not produce a capsule.…”
Section: Discussionmentioning
confidence: 98%
“…These species names do not represent good monophyletic groups, so it is difficult to distinguish them using chromosomal genetic typing methods (Helgason et al, 2000;Vilas-Boas et al, 2007;Raymond et al, 2010a). However, phylogenetic analysis of strains characterized by multiple locus sequence typing suggests that closely related strains are likely to have similar ecology or host association (Guinebretière et al, 2010;Raymond et al, 2010b;Raymond and Bonsall, 2013a). In this study, we identified LM1212 as a strain of Bt, based on both genetic typing methods (Supplementary Figure S3; Supplementary Table S3) and phenotypic identification (Figures 1b and 2; Supplementary Figures S2A and B).…”
Section: Discussionmentioning
confidence: 99%